Question analysis of mathematics textbook for 2013 curriculum and IB curriculum on quadratic equations - Raditya, Aji; Iskandar, Ratu Sarah Fauziah; Suwarno, Suwarno (Universitas Islam Negeri Raden Intan Lampung, 2021)
The goal of this study is to compare the types of questions between the 2013 Curriculum Mathematics textbooks and the IB Curriculum on quadratic equations. The approach used in this research is a six-dimensional analysis method consisting of: mathematical activity, the difficulty level of the questions, the types of answers expected, the contextual situation, the types of responses, and the stages of the mathematical questions. The data collection technique is conducted by evaluating and explaining the types of questions. The types of questions were obtained from the 2013 Curriculum Mathematics textbook and the IB Curriculum based on a six-dimensional analysis, namely: mathematical activity, question complexity, type of answer, contextual situation, type of response, and mathematical questions. Based on the type, the results of this study show that the questions in the 2013 curriculum mathematics textbooks are more varied than the questions in the IB curriculum mathematics textbooks on the subject of quadratic equations. However, based on the number, there are more questions in the IB curriculum mathematics textbook than the questions in the 2013 curriculum mathematics textbook.